Використання праці радянських військовополонених у промисловості та сільському господарстві під час нацистської окупації України - Богунов, С. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The present article is the complete version of paper for international conference “War capture and the return home of soviet and German prisoner of war. 1945–1955” (Federal Republic of Germany, April, 2005). Based on the documents of Branch state archive of Security service of Ukraine, the article investigated the usage of Soviet prisoners of war labour in the industry and agriculture.